Cumulant Representation of Solutions of the BBGKY Hierarchy of Equations - Gerasimenko, V. I.; Ryabukha, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We construct a cumulant representation of solutions of the Cauchy problem for the BBGKY hierarchy of equations and for the dual hierarchy of equations. We define the notion of dual nonequilibrium cluster expansion. We investigate the convergence of the constructed cluster expansions in the corresponding functional spaces.